Pengaruh KDRT Terhadap Pertumbuhan Anak - Aulia Rexana Sitaresmi; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Domestic violence (DV) is a serious issue with widespread impacts, especially on children who are victims or witnesses. The effects of DV on children encompass physical, psychological, and social aspects. Children exposed to DV often experience trauma, developmental disorders, and mental health issues such as anxiety and depression. Additionally, they are at high risk of experiencing violence in the future, either as victims or perpetrators. Legal efforts to protect children from DV in Indonesia are regulated by various laws, including Law No. 23 of 2004 on the Elimination of Domestic Violence and Law No. 35 of 2014 on Child Protection. These regulations provide a strong legal foundation for handling DV cases, including the arrest of perpetrators, provision of legal assistance, and protection of victims’ identities. The rehabilitation process for child victims of DV involves physical recovery through medical care and psychosocial support such as counseling and therapy to help children overcome trauma and rebuild a sense of safety. Support from social workers and legal assistance is also crucial to ensure children’s rights are fulfilled and they receive adequate protection. Collaboration between the government, non-governmental organizations, and the community is essential in addressing DV. Efforts to prevent and address DV must include raising public awareness, strengthening the legal framework, and providing effective support services.